Human Colorectal Cancer from the Perspective of Mouse Models - Stastna, Monika; Janeckova, Lucie; Hrckulak, Dusan; Kriz, Vitezslav; Korinek, Vladimir (Genes, 2019)
Colorectal cancer (CRC) is a heterogeneous disease that includes both hereditary and sporadic types of tumors. Tumor initiation and growth is driven by mutational or epigenetic changes that alter the function or expression of multiple genes. The genes predominantly encode components of various intracellular signaling cascades. In this review, we present mouse intestinal cancer models that include alterations in the Wnt, Hippo, p53, epidermal growth factor (EGF), and transforming growth factor β (TGFβ) pathways; models of impaired DNA mismatch repair and chemically induced tumorigenesis are included. Based on their molecular biology characteristics and mutational and epigenetic status, human colorectal carcinomas were divided into four so-called consensus molecular subtype (CMS) groups. It was shown subsequently that the CMS classification system could be applied to various cell lines derived from intestinal tumors and tumor-derived organoids. Although the CMS system facilitates characterization of human CRC, individual mouse models were not assigned to some of the CMS groups. Thus, we also indicate the possible assignment of described animal models to the CMS group. This might be helpful for selection of a suitable mouse strain to study a particular type of CRC.
Keywords: epidermální růstový faktor; regulace genové exprese u nádorů; Humans; nádory tračníku; Genes, p53; Carcinogenesis; Colonic Neoplasms; geny p53; protein-serin-threoninkinasy; lidé; Epidermal Growth Factor; zvířata; myši; nádorová transformace buněk; Mice; Wnt Signaling Pathway; signální dráha Wnt; Protein Serine-Threonine Kinases; kolorektální nádory; karcinogeneze; DNA Mismatch Repair; transformující růstový faktor beta; Cell Transformation, Neoplastic; oprava chybného párování bází DNA; Transforming Growth Factor beta; Animals; Gene Expression Regulation, Neoplastic; Disease Models, Animal; Colorectal Neoplasms; modely nemocí na zvířatech